Erbliche Sehnerverkrankungen - Rüther, Klaus (Klinische Monatsblätter für Augenheilkunde, 2018)
Trotz der Seltenheit haben die erblichen Sehnerverkrankungen den Vorteil, dass sie oftmals durch die Anamnese erkannt werden können und die Diagnosesicherung heute sicher durch eine molekulargenetische Untersuchung geleistet werden kann. Als isolierte erbliche Sehnerverkrankungen sind im augenheilkundlichen Alltag die Leberʼsche hereditäre Optikusneuropathie (LHON) und die autosomal-dominante Optikusatrophie (ADOA) relevant.Hereditary optic nerve disorders are rare. For ophthalmologists, Leberʼs hereditary optic neuropathy (LHON) and autosomal dominant optic atrophy (ADOA) are of particular relevance. LHON and ADOA are diseases of the retinal ganglion cells and are caused by mitchochondrial dysfunction. LHON is based on mutations of the mitochondrial, ADOA of the nuclear DNA. LHON is a disease that usually leads to severe visual impairment (visual acuity < 0.1). Since there is an approved therapy for LHON (Idebenone [Raxone]), the diagnosis has to be confirmed immediately by means of molecular genetic diagnostics. ADOA usually shows less severe visual impairment, begins in childhood, and progresses gradually, often for a long time without any noticeable worsening. Family history (dominant heredity) and blue colour vision disorder are the leading indicators for the diagnosis of ADOA, which should be confirmed by molecular genetic testing. Optic nerve diseases can also occur in the context of hereditary, syndromic disorders. Ophthalmologically relevant are Wolfram syndrome, Friedreichʼs ataxia and Charcot-Marie-Tooth disease. In all hereditary optic nerve disorders, foods containing cyanide and smoking should be avoided. Excessive alcohol consumption is considered to be a trigger of LHON and possibly harmful in other hereditary optic neuropathies. In the management of patients with hereditary optic nerve disorders, aspects of rehabilitation as well as social and psychological care should be considered.
Keywords: erbliche Optikusneuropathien; Optikusatrophie; Leberʼsche hereditäre Optikusneuropathie; autosomal-dominante Optikusatrophie; Mitochondriopathie